Effects of Climate Change on Agricultural Calendar in the North of Iran - mojtaba shahnazari; Zahra Hejazizadeh; Mohammad Saligheh (تحقیقات کاربردی علوم جغرافیایی)
Abstract In this research, while studying climate conditions in the current period and analyzing changes in temperature, precipitation level, and the sunlight received, current conditions were also analyzed based on daily data from synoptic stations in the region, which had meteorological data recorded for at least 30 years. Given the environmental conditions necessary for the growth of rice, the availability of its phenological data, its high-low temperature thresholds, the Degree Day systems needed for the completion of its life cycle, and the phenological processes related to its economic production, a suitable agricultural calendar was specified. During the March-July period, this calendar showed variations in different provinces. Based on the current temperature conditions and the probable continued warming trend of the planet in the decades to come, nwoDscale was applied to the output from the atmospheric general circulation model MCdaH3 under  scenario using LARS-WG5 model. In this study, years between 1969 and 1990 were used as the base period, while years between 2046 and 2065 were studied as the future period. Temperature and precipitation conditions for the future period were simulated. Obtained output was then studied and compared with temperature conditions that were suitable for the plant to grow in the region. With some differences, results showed that the agricultural calendar for rice in Gilan and Mazandaran provinces will shift to winter. Given the different temperature conditions of Golestan province, its agricultural calendar will shift to spring.